Novel Concepts in the Immunology and Treatment of Vascularized High Risk Corneal Allotransplants - Carlos Alonso Medina; Sander R Dubovy; Eduardo Alfonso; Payman Haft; Victor L Perez (Vision Pan-America, 2012)
Corneal allotransplantation has been the principal surgical treatment for vision loss caused by diseases of the cornea that result in scarring and opacification. Most authors define a “high risk” cornea as that of a previously failed corneal graft or a cornea with vascularization in at least 2 quadrants.  These high-risk corneal transplants have rejection rates approaching 70% even with maximal local and systemic immune suppression. The management of high risk corneal transplants, which until recently was a slowly evolving field in ophthalmology, remains a highly controversial yet important topic. Management of these high risk transplants has developed rapidly in the past 10 years. In this review, some of the challenges and controversies associated with high risk corneal allotransplantation therapy will be discussed.